(untitled) (SCIENCE TIME JOURNAL, 2026)
This article investigates the integration of artificial intelligence tools into translator education, examining both the opportunities these technologies present and the pedagogical challenge. As neural machine translation systems, AI-assisted computer-aided translation platforms, and large language models become increasingly prevalent in professional translation practice. Drawing on a review of recent empirical studies and theoretical frameworks in translation pedagogy, this article analyzes the impact of AI tools on key aspects of translator education, including competence development, post-editing skill acquisition, and critical evaluation. The findings suggest that AI tools, when integrated thoughtfully and critically, can enhance the learning process by exposing trainees to authentic professional workflows